Firebase Realtime Database Untuk Aplikasi Point of Sales UMKM Berbasis Cloud Computing Pada Smartphone Android - Rangga Gelar Guntara (Impression : Jurnal Teknologi dan Informasi, 2022)
Currently, micro, small and medium enterprises (MSMEs) make payment transactions at the cashier still manually. This creates many obstacles and problems, for example the management of transaction data is not carried out properly. With the rapid development of MSMEs today, business actors are required to be able to think as creatively as possible in running their business. One of the factors so that MSME businesses can develop and have strong competitiveness is good transaction management and business information. It takes a technology-based computing and informatics to reduce the problems in the MSME business actors. One of them is by utilizing cloud computing technology. Cloud computing is present as a technology that is able to solve the problem of efficiency and flexibility. This research will utilize the firebase realtime database as a product of cloud computing technology to answer the problems of MSME business actors. Problems, especially in payment transactions at the cashier to further improve customer convenience. Based on the results of research and testing of software on the android platform that has been discussed, the results of the research have been able to design a payment transaction application system for MSMEs by utilizing cloud computing and android-based realtime firebase. The suggestions for software development are to improve features and other data needed such as making more detailed financial reports.